Research on Dust Suppression Technology of Shotcrete Based on New Spray Equipment and Process Optimization - Pengcheng Li; Zhi Zhou; Lianjun Chen; Guoming Liu; Wei Xiao (Advances in Civil Engineering)
In order to reduce the dust hazard of shotcrete, the paper analyzed the mechanism of dust production from the perspective of various dust sources and developed the plunger-type wet spraying machinery and wet mixer which can be applied in the small-section tunnel for reducing dust on the root cause. The dust concentration between dry-mix shotcrete and wet-mix shotcrete was compared and analyzed. The results showed that the average total dust concentration and respirable dust concentration in the process of dry spraying were 99.4 mg/m3 and 52 mg/m3, respectively, while 9.8 mg/m3 and 4.08 mg/m3 in the wet-mix shotcrete process, and the average dust concentration decreased by more than 90% after applying new wet-mix shotcrete outfits. The clean zone of dust was divided according to the dust distribution. Finally, the dust suppression technology was optimized by using an accelerator and adjusting wind pressure and spraying angle. Results indicated that the application of the accelerator reduced the dust production efficiently; moreover, when the wind pressure was 0.2 MPa with 1 m spraying distance and 90° angle of spraying, the dust concentration and rebound reached the minimum.